Drivers and Changes of the Poyang Lake Wetland Ecosystem - Wang, Yuyu; Molinos, Jorge García; Shi, Linlu; Zhang, Min; Wu, Zhaoshi; Zhang, Huan; Xu, Jun (Wetlands (Wilmington, N.C.), 2019)
This paper serves as both a review of the latest science on the Poyang Lake wetland ecosystem and as an introduction to this Special Issue guest-edited by Jun Xu. Poyang Lake is the largest freshwater lake in China and one of the largest freshwater lake/wetland complexes in Asia. Poyang Lake’s associated floodplain wetlands play a critical role for regional and global biodiversity conservation, particularly wintering migratory birds. Since the Three Gorges Dam became operative in 2003, the magnitude and frequency of extreme seasonal water-level fluctuations in Poyang Lake have increased significantly. We review the existing literature and contributions to this Special Issue on the Poyang Lake wetland ecosystem and their biota in relation to impacts from the Three Gorges Dam. Resulting impacts on, and adaptations of, Poyang Lake biota to the hydrological changes caused by operation of the dam are poorly understood. Adaptive management of this lake and its associated wetlands needs to be further assessed through comprehensive, long-term monitoring covering a wide range of parameters related to the system’s hydrological characteristics, water quality, geomorphology, aquatic biota, wetland vegetation, and associated wetland fauna.